Human Resource Management Competencies in Supporting Blue Economy Policies in the Coastal Tourism Sector of Tolitoli Regency - Fiansi; Mirayanti; Rukhayati (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Palu, 2025)
This study aims to analyze human resource management competencies in supporting the implementation of Blue Economy policies in the coastal tourism sector of Tolitoli Regency. A descriptive qualitative approach was employed by involving 15 respondents consisting of local government officials, coastal tourism business actors, and coastal community representatives. Data were collected through in-depth interviews, field observations, and documentation studies, and analyzed using an interactive process of data reduction, data display, and conclusion drawing. The findings indicate that human resource competencies in terms of knowledge, skills, and attitudes play a strategic role in supporting the Blue Economy; however, conceptual understanding and managerial skills related to sustainable coastal tourism remain limited. Although positive attitudes and commitment toward environmental conservation are evident, their practical implementation has not been optimal due to limited institutional support and weak cross-sectoral coordination. This study recommends strengthening Blue Economy policy literacy, enhancing sustainable human resource capacity development, and improving stakeholder coordination to promote sustainable coastal tourism development in Tolitoli Regency.